Peningkatan Motivasi Belajar Peserta Didik Melalui Pendekatan Bimbingan Kelompok - Dwi Endang Sri Suharini (Jurnal Kreatif Online, 2021)
The purpose of this study was to determine the increase in student motivation in class XI TKJ SMKN 1 Palu through group guidance services. The subjects of this study were students of class XI TKJ B SMKN 1 Palu, totaling 28 people. This counseling guidance action research consists of two cycles. The instrument used is a student learning motivation questionnaire using positive statement sentences, so that the answer always (SL) has a score of 4, often (SR) has a score of 3, rarely (JR) has a score of 2 and never (TP) has a score of 1. Success criteria This action research is an increase in students' learning motivation which is marked by the achievement of indicators of learning motivation, namely the average student reaches 75%. Based on the data analysis carried out, the results obtained in the first cycle, students' learning motivation is in the high category with a percentage of 7.14%, the high category is 57.14% while the medium and low categories are 21.42% and 14.28% respectively. . In the second cycle there was an increase where the students' motivation was in the very high category and the high category with the percentages of 46.42% and 53.58%, respectively. The medium, low and very low categories were no longer found in cycle II. The increase in student motivation in class XI TKJ SMKN 1 Palu occurred because of the application of the group guidance approach.